FACTORS AFFECTING MOTHERS WHO HAVE BABIES IN EXCLUSIVE BREAST FEEDING IN ASUHAN VILLAGE SIANTAR TIMUR DISTRICT PEMATANG SIANTAR CITY - Yulia Delfahedah; Wilson Samosir; Arsiaty Sumule (Universitas Efarina, 2021)
Exclusive breastfeeding is very important for the growth and development of infants, and is also important for the future of the nation and state. So the researcher is interested in conducting research on the factors that influence mothers who have babies in exclusive breastfeeding in the Asuhan Village, Siantar District, Pematangsiantar City Team in 2016. were mothers who had babies 0-6 months as many as 300 people. The sample size was 166 people using the formula from the Lemenshow books. The results of this study were the majority of respondents having high school education, namely 66 people (39.8%), while the minority had elementary education, namely 25 people ( 15, 1%) The majority have jobs as private employees, namely 49 oning (29.5%), while a minority have jobs as housewives, namely 49 people (29.5%). The majority have good knowledge, namely 95 people (57.2%), while the minority have less knowledge, namely 71 people (42.8%). The majority had an attitude of agreement, namely 117 people (70.5%), while the minority had less knowledge, namely 71 people (29.5%). Mothers have a very important role in exclusive breastfeeding, for that mothers must be able to properly manage the time of exclusive breastfeeding.